Living between mountains: joys and sufferings in the Sanatorio Durán - Barquero Morice, Pablo (2018)
This article wants to analyze the daily life in the Sanatorium Carlos Durán Cartín when it was used as a sanatorium for people suffering from tuberculosis, by means of written documents between a patient and his friend. These relate the experiences and misfortunes that occurred during the eight months of internment due to the medical protocol of the place, allowing to appreciate from a new perspective the experiences of those who inhabited this site and the medical advances in the fight against tuberculosis within the Sanatorium Carlos Durán Cartín. Although these written documents cease to appear for reasons that are not explained in them, they are clear enough to infer conclusions related to the vision of the Sanatorium as a center of medical excellence at national and Central American level but that it probably was not a place that was within reach of anyone because of the high costs of treatment that in some cases, the patient had to cover.